2016
DOI: 10.1111/jocn.13173
|View full text |Cite
|
Sign up to set email alerts
|

It is important that they care – older persons’ experiences of telephone advice nursing

Abstract: The communicative competence of telephone nurses is essential when providing telephone advice nursing to older persons. In addition, a person-centred approach is important to provide optimal care in telephone advice nursing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
104
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(105 citation statements)
references
References 22 publications
1
104
0
Order By: Relevance
“…Other studies have also found that telenurses experienced that parents were insecure and anxious about their sick children and parents described that monitoring calls could be reassuring when the encounter was experienced as being respectful and providing opportunities to share their worries . Creating trust early in the conversation seemed to enable a mutual understanding and a sense of security . A monitoring call can be understood as a caring meeting where the professional care is carried out by telephone, as described by Halldorsdottir .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have also found that telenurses experienced that parents were insecure and anxious about their sick children and parents described that monitoring calls could be reassuring when the encounter was experienced as being respectful and providing opportunities to share their worries . Creating trust early in the conversation seemed to enable a mutual understanding and a sense of security . A monitoring call can be understood as a caring meeting where the professional care is carried out by telephone, as described by Halldorsdottir .…”
Section: Discussionmentioning
confidence: 99%
“…Around half of the calls resulted in self‐care advice, and these care‐seekers were not referred to any other healthcare service . Research from the past decade shows that care‐seekers call to gain a sense of security and that adequate advice and professional and friendly care from the telenurses were important .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To accomplish this, despite the lack of visual contact and the relatively short encounter with TAN, telenurses require special knowledge in communication. Therefore, researchers highlight the telenurse's communication and interpersonal competence (Barbosa et al 2016;Holmström et al 2016;Larson-Dahn 2000;Röing & Holmström 2015;Snooks et al 2008;Wahlberg et al 2005;Valanis et al 2007). Communication competence is sometimes defined in terms of specific tasks such as using effective questioning skills to interview the caller, whereas interpersonal competence can be described as a process of interaction that includes treating the caller with respect, expressing empathy, paying attention, and demonstrating a caring attitude (Duffy et al 2004).…”
Section: Figure 1 Interaction Model Of Client Health Behaviormentioning
confidence: 99%
“…The quality of information is important for gaining callers' trust (Pettinari & Jessop, ). Callers experience safety and satisfaction when they perceive that they are the most important person in the conversation and communication with the telephone nurse is good (Holmström, Nokkoudenmäki, Zukancic, & Sundler, ).…”
Section: Introductionmentioning
confidence: 99%